Unilateral regressed ovary in farm reared Labeo rohita(Ham.) - Rath, S C; Mondal, B; Sarkar, S K; Gupta, S D (Indian Journal of Fisheries, 2011)
Unilateral regressed ovary in farm reared Labeo rohita(Ham.)